TEACHER’S STRATEGY IN MAINTAINING THE FLOW OF STUDENTS’ ENGLISH INTERACTION IN SPEAKING CLASS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2016)
This qualitative mini-research aimed to reveal the strategy used by a teacher in speaking class. The researcher observed a teacher in one of the private university in Makassar for three meetings in a speaking class. In addition, the researcher did an interview with the teacher and her fifteen students who attended in her class. The finding implied that the teacher employed communicative approach by giving pair and group work activities. She also applied a rule Don’t Speak in Bahasa (no one is allowed to speak in Indonesia including herself) with reward and punishment. Moreover, the interview indicated that the teacher’s strategy in speaking class motivated the students to speak fully in English and built up their confidence. Keywords: speaking, strategy, rule.